Properties of Silver Nanoparticles Prepared by the Electric Spark Dispersion Method; Advanced Materials Research; Vol. 872 - Zhuravkov S. P. Sergey Petrovich; Plotnikov E. V. Evgeny Vladimirovich; Martemyanov D. V. Dmitry Vladimirovich; Yavorovsky N. A. Nikolay Aleksandrovich; Hasse U.; Zander S. (2014, 2014)
Title screen